Numerical analysis of the internal flow and pressure pulsation characteristics of a submersible tubular electric pump device - Lv, Yuting; Ding, Ping; Liu, Jinsheng; Ge, Hengjun; Yang, Fan; Tang, Fangping (Frontiers in Energy Research, 2023)
In order to clarify the non-constant flow characteristics of the impeller and bulb body of the submersible tubular electric pump device, the entire flow rate conduit of the pump device is numerically calculated using the numerical simulation method, focusing on the analysis of the non-constant flow field characteristics of the guide vane body and bulb body and the time-frequency variation law of the pressure pulsation, and the results of the physical model testing confirm the validity of the numerical simulation. The findings demonstrate that the impeller of a submersible tubular electric pump is mostly responsible for the impeller's inlet pressure pulsation, and the number of impeller blades to the number of peaks and valleys is consistent. Under the high flow rate condition of 1.2Qd, the pressure pulsation between impeller inlet, reduced fluctuation in the impeller and guiding vane body, the main frequency is located at 3 times the rotational frequency, and the pressure pulsation at the outlet of guide vane body has no obvious pattern and small amplitude. As the flow rate increases, the peak value of pressure pulsation at each monitoring point in the characteristic section of the pump device gradually decreases. The pressure pulsation peak value varies widely, ranging from 0.058 to 0.15, at each monitoring location of the impeller inlet. The peak value of pressure pulsation at each monitoring point of the impeller outlet fluctuates less due to the change of flow rate. The size and scale of omega vortex structure in the guide vane body at different moments of the same cycle is small, and the number of vortex structures from the guide vane body inlet to the outlet direction shows a gradual increase in the trend; with a rise in flow rate, there is a tendency for the velocity and deflection angle of the guide vane body outlet and bulb body outlet surface to decrease.